NLRP6 negatively regulates type 2 immune responses in mice. Issue 11 (10th June 2022) - Chenuet, Pauline; Marquant, Quentin; Fauconnier, Louis; Youness, Ali; Mellier, Manon; Marchiol, Tiffany; Rouxel, Nathalie; Messaoud‐Nacer, Yasmine; Maillet, Isabelle; Ledru, Aurélie; Quesniaux, Valérie F. J.; Ryffel, Bernhard; et al.
Abstract: Background: Inflammasomes are large protein complexes that assemble in the cytosol in response to danger such as tissue damage or infection. Following activation, inflammasomes trigger cell death and the release of biologically active forms of pro‐inflammatory cytokines interleukin (IL)‐1β and IL‐18. NOD‐like receptor family pyrin domain containing 6 (NLRP6) inflammasome is required for IL‐18 secretion by intestinal epithelial cells, macrophages, and T cells, contributing to homeostasis and self‐defense against pathogenic microbes. However, the involvement of NLRP6 in type 2 lung inflammation remains elusive. Methods: Wild‐type (WT) and Nlrp6 −/− mice were used. Birch pollen extract (BPE)‐induced allergic lung inflammation, eosinophil recruitment, Th2‐related cytokine and chemokine production, airway hyperresponsiveness, and lung histopathology, Th2 cell differentiation, GATA3, and Th2 cytokines expression, were determined. Nippostrongylus brasiliensis ( Nb ) infection, worm count in intestine, type 2 innate lymphoid cell (ILC2), and Th2 cells in lungs were evaluated. Results: We demonstrate in Nlrp6 −/− mice that a mixed Th2/Th17 immune responses prevailed following birch pollen challenge with increased eosinophils, ILC2, Th2, and Th17 cell induction and reduced IL‐18 production. Nippostrongylus brasiliensis infected Nlrp6 −/− mice featured enhanced early expulsion of the parasite due to enhanced type 2 immune responses compared to WT hosts. In vitro, NLRP6 repressed Th2 polarization, as shown by increased Th2 cytokines and higher expression of the transcription factor GATA3 in the absence of NLRP6. Exogenous IL‐18 administration partially reduced the enhanced airways inflammation in Nlrp6 −/− mice. Conclusions: In summary, our data identify NLRP6 as a negative regulator of type 2 immune responses. Abstract : Birch pollen extract exposure results in elevated eosinophilic airway inflammation and type 2 immune responses. Birch pollen induces NLRP6 inflammasome activation and the release of mature IL‐18 in the lung. NLRP6 negatively regulated mixed Th2/Th17 immune responses to birch pollen induced lung inflammation and helminth infection.Abbreviations: BPE, birch pollen extract; EOS, eosinophil; GATA3, GATA binding protein 3; ILC, innate lymphoid cell; i.n., intranasal; i.p., intraperitoneal; N. brasiliensis; Nippostrongylus brasiliensis ; NLRP6, NOD‐like receptor family pyrin domain containing 6; rIL‐18, recombinant interleukin 18; s.c., subcutaneous; Th, T helper cell; WT, wild type